L’efficacité des études en France pour améliorer les compétences linguistiques en français des étudiants indonésiens - Sarah Mumtazah; Dwi Astuti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This study examines the effectiveness of the Bourse Français Langue Étrangère (Bourse FLE) program in improving the linguistic competence of Indonesian students. The scholarship (bourse), offered by the Institut Français d’Indonésie (IFI), supports the French acquisition through immersive learning at Université Paul-Valéry Montpellier 3. Seven Indonesian students participated in this intensive program. A quantitative experimental method was applied using pre- and post-tests. The curriculum included phonetics, grammar, oral and written comprehension and production, conversation workshops, and weekly cultural excursions. The t-test showed a significance value of 0.030 < 0.05, indicating a notable improvement. About 86% of students passed the final exam. Three students (43%) progressed from B1 to B2, although average scores declined due to exam difficulty. Two students (B1-B1) and one (B2-B2) demonstrated significant improvement (43), especially in oral comprehension, oral production, and written comprehension. One B1-level student showed no improvement. These findings confirm that the FLE program is effective in improving the linguistic competence of Indonesian students through immersive acquisition de français.